To the question about prospects (upcycle) of abandoned copper-sulphide pits in the Urals - Karagodin Sfen Stepanovich; Karagodin Vladimir Sfenovich; Morozov Yuriy Petrovich; Zauzolkov Ivan Vasil'Evich (Федеральное государственное бюджетное образовательное учреждение высшего образования «Уральский государственный горный университет», 2018)
Relevance of the topic is due to concern of modern civilized society about the negative impact on the ecology of man-made mineral formations of the mining activity. Technogenic ores are represented by sludges, which are removed by groundwater from abandoned pits and rock dumps. They are deposited in surface watercourse and serve as a source of environmental disasters. They overfill natural and artificial sedimentation basin, and the mine waters carrying them threaten to increase acidity in protected reservoirs that serve as a source for drinking water for big cities. At the same time, in recent years, the industrial value of these sludges has been determined, and the technology has been developed for extracting non-ferrous metals and useful associated components from them. It is revealing that this ore sludge occur directly in alluvial and deluvial deposits of river valleys and ponds, which are also of industrial interest as a source of surface gold and industrial minerals sand gravel mixes. The need for the extraction of large volumes of the latter is particularly relevant, since an extensive construction program is planned and implemented here. The purpose of this paper is to attract attention of business and the public to an economically advantageous project for the development of man-made copper-zinc ores from the abandoned pits of the Urals with a simultaneous solution of environmental problems. Methodology. The work was done by the authors using the results of their own research and materials in collaboration with the team of Nedra group Ltd. The result of the work. The authors have shown the presence of technogenic copper-zinc deposit within the territory of the Degtyarsky pit and predicted gold-bearing placers in addition to it. Conclusions. The main task of the study in the territory of the Degtyarsky pit is granting the licenses for the sites of Istok and Elchyovka; the estimated cost of engineering design and geological exploration with an evaluation of reserves of non-ferrous, noble metals and associated raw materials in sludge and alluvium-deluvium, as well as with the solution of environmental problems, ranges from 50-60 to 80 million rubles.
Keywords: TECHNOGENIC AND COMPLEX DEPOSIT; COPPER-ZINC ORES; ALLUVIAL GOLD; INDUSTRIAL MINERALS; ECONOMICS; ECOLOGY; ТЕХНОГЕННОЕ МЕСТОРОЖДЕНИЕ; КОМПЛЕКСНОЕ МЕСТОРОЖДЕНИЕ; МЕДНО-ЦИНКОВЫЕ РУДЫ; АЛЛЮВИАЛЬНОЕ ЗОЛОТО; СТРОИТЕЛЬНЫЕ МАТЕРИАЛЫ; ЭКОЛОГИЧЕСКИЕ ПРОБЛЕМЫ; 553.3.072; 071